Analisis Potensi Pengelolaan Sampah Organik Sebagai Energi Alternatif Biogas Terbarukan - Aqilah, Dayang Nur; ., Yushardi; ., Sudarti (CV. ITTC INDONESIA, 2023)
Indonesia is a country with rapid population growth. With ongoing population growth, the percentage of waste growth in Indonesia is getting higher. Waste is classified into organic and non-organic waste. The waste management system is still less effective and efficient. Piles of rubbish have the potential to produce gases that are dangerous to health. One effort to handle waste is to convert waste into renewable alternative energy. The aim of this research is to determine the potential of organic waste in Indonesia. So that the existing potential can be converted into an alternative biogas energy. This research provides insight into dealing with the potential for managing organic waste as sustainable energy and can reduce the percentage of waste in Indonesia.